Effect of variation in gridded cattle diet composition on estimated enteric methane emissions in data sparse tropical regions - J.Y. Mutua; A.J. Duncan; T.P. Robinson; S. Fraval; A.M.O. Notenbaert; G.R. Watmough (Animal)
Livestock directly contribute to greenhouse gas emissions, mainly through enteric fermentation and to a lesser extent manure management. Livestock feed composition plays a crucial role in diet quality and the resulting emissions from livestock. Diet composition varies seasonally particularly in tropical environments with long dry periods. However, existing data have uncertainties resulting from data collection challenges and the assumption of a constant annual distribution of diet composition. This study investigated the potential impact of spatial and temporal variations in livestock feed composition on diet quality and enteric methane emissions in Kenya, as a case study. Spatially explicit data on crop distribution and land use were combined with feed quality data to generate livestock diet composition maps. Results indicate that current livestock emission estimates can vary considerably from Intergovernmental Panel on Climate Change (IPCC) default values depending on the location and season. Average livestock diet quality expressed as dry matter digestibility (DMD) was estimated to be 56.7% which was greater than the default digestibility value of 55.0% set by the IPCC for livestock production systems in the region. Estimated minimum and maximum DMD differed within and between livestock production systems demonstrating uncertainty and potential spatial and temporal variability. Estimated enteric methane emissions from cattle varied between and within livestock production systems (37.1 – 72.8 kg CH4/head per year), with significant differences between mixed rainfed humid and temperate production systems (P < 0.05). Overall, these variations should be considered when estimating greenhouse gas emissions from livestock production systems. It is crucial to revise default values for production systems to improve results from livestock emission models, thus informing better national-level strategies for emission reduction.